A survey of therapists views on reducing sedentary behaviour in an acute clinical setting - Juliet A Harvey; Joanna R McBain; Heather Cameron (AIMS Medical Science, 2018)
Reducing sedentary behaviour is a priority in both the clinical and research settings. This survey aimed to gather the views on reducing sedentary behaviour from physiotherapy, occupational therapy and healthcare support staff working in the acute healthcare setting. Sixty-nine occupational therapy and physiotherapy staff completed an online survey during March and April 2018. The results were analysed by manual thematic analysis. Barriers to sedentary behaviour have been categorised under the following themes: patient factors, cultural factors, environmental factors and organisational factors. Solutions to facilitate change were themed as: move early and often, self-management, education, culture, environment, collaboration, social engagement, roles and sharing. The findings provide a basis for changing behaviour from a practitioner perspective.